2016
DOI: 10.1002/jso.24153
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in patients with liver involvement

Abstract: Liver involvement denotes high peritoneal carcinomatosis burden, which often requires resection of multiple organs in order to achieve optimal cytoreduction. However, liver resection-related morbidity is low and overall morbidity/mortality rates are comparable to other extensive CRS/HIPEC procedures. J. Surg. Oncol. 2016;113:432-437. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…As CRS with HIPEC has an overall morbidity rate of 23–45% and mortality rate of 0–12% in CRC patients with peritoneal metastasis only, the addition of concurrent liver resection does not seem to reduce safety [25]. Berger et al suggested that perioperative complication rate, length of hospital stay, and intraoperative blood transfusion were related to more extensive cytoreduction, rather than liver surgery itself [26]. In our study, only one patient died of intestinal anastomotic leakage; she had three anastomoses, which was relatively higher compared to other patients, without stoma diversion.…”
Section: Discussionmentioning
confidence: 99%
“…As CRS with HIPEC has an overall morbidity rate of 23–45% and mortality rate of 0–12% in CRC patients with peritoneal metastasis only, the addition of concurrent liver resection does not seem to reduce safety [25]. Berger et al suggested that perioperative complication rate, length of hospital stay, and intraoperative blood transfusion were related to more extensive cytoreduction, rather than liver surgery itself [26]. In our study, only one patient died of intestinal anastomotic leakage; she had three anastomoses, which was relatively higher compared to other patients, without stoma diversion.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 3137 patients participated in 2 case-control studies, 11 prospective studies, and 7 retrospective cohort studies. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] No randomized studies were identified. Although the search and selection process was designed to include various oligometastatic sites, the studies that met the criteria for inclusion all presented liver metastases.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These data are reassuring given concomitant HM, in most cases, represent both systemic and loco‐regional disease. Some series have reported that synchronous HM compromise outcomes . Randle and colleagues reported a median OS of 21.2 months for patients with HM compared to 33.6 months for those without HM ( P = 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated that concomitant HR increases peri‐operative morbidity and compromises survival outcomes . Others have shown that concomitant HR is safe and effective .…”
Section: Introductionmentioning
confidence: 99%